Respuesta :
Step-by-step explanation:
3
√
2
2
⋅
2
Pull terms out from under the radical.
3
(
2
√
2
)
Multiply
2
by
3
.
6
√
2
The result can be shown in multiple forms.
Exact Form:
6
√
2
Decimal Form:
8.48528137
…
For this case we must simplify the following expression:
[tex]3 \sqrt {2} +3 \sqrt {8}[/tex]
We rewrite:
[tex]8 = 2 ^ 3 = 2 ^ 2 * 2\\3 \sqrt {2} +3 \sqrt {2 ^ 2 * 2} =[/tex]
For properties of potecnias and roots we have that:
[tex]\sqrt [n] {a ^ m} = a ^ {\frac {m} {n}}[/tex]
Then, rewriting the expression:
[tex]3 \sqrt {2} + 2 * 3 \sqrt {2} =\\3 \sqrt {2} +6 \sqrt {2} =\\9 \sqrt {2}[/tex]
Answer:
[tex]9 \sqrt {2}[/tex]